2015
DOI: 10.1002/adem.201400542
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Scanning Strategy on the Microstructure and Mechanical Properties in Selective Electron Beam Melting of Ti–6Al–4V

Abstract: Selective electron beam melting (SEBM) is perhaps the fastest production process for additive manufacturing techniques from powder beds. In the present investigation, scan speeds of 10 m s À1 have been used successfully for the melting. Nevertheless, the beam power has to be adjusted to guarantee a density of more than 99.5% for the build samples. The aim of this paper is to investigate the effect of the scan speed and beam power on the microstructure and the mechanical properties of Ti-6Al-4V. Therefore, a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…For example, the α lamellar spacing can vary significantly along the build direction [13,14], since the local thermal conditions are affected by the position within the part relative to the heat flux through the build plate. Scharowsky et al have also shown that in EBM the lamellar plate spacing increases with the energy volume density of the heat source [30].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, the α lamellar spacing can vary significantly along the build direction [13,14], since the local thermal conditions are affected by the position within the part relative to the heat flux through the build plate. Scharowsky et al have also shown that in EBM the lamellar plate spacing increases with the energy volume density of the heat source [30].…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, in finer scale AM processes like EBM the transformation microstructure is considered to be more homogeneous because of greater thermal field overlap between multiple tracks and, particularly in the case of EBM, where high build temperatures are used [7,12,8]. However, it is still known to be sensitive to the part geometry [7,11], beam scan control algorithms [11,14,30] build temperature [12] and height [7,13,14]. For example, the α lamellar spacing can vary significantly along the build direction [13,14], since the local thermal conditions are affected by the position within the part relative to the heat flux through the build plate.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2012) showed that increasing the energy density (high power and low scan speed) allows mitigating or avoiding this kind of defect. Regarding EBM, different authors (Scharowsky et al (2015), Zaeh and Kahnert (2009), Puebla et al (2012), Tammas-Williams et al (2015) and Biamino et al (2011) studied the importance of process parameters and scanning strategy of part density, pore morphology and part performances.…”
Section: Processmentioning
confidence: 99%
“…Changing process parameters such as laser power and scanning parameters, specifically scanning speed and its effects on energy density, has been shown to cause a considerable change in the grain structure (Gong et al, 2014b), the phases present (including the promotion of metastable phase formation), their distribution within the microstructure (Scharowsky et al, 2015), and tendencies for defect generation (Zhong et al 2015) in AM parts (Liang et al, 2014a(Liang et al, , 2014b. The variation in the temperature gradient in the melt pool result in variation in the solidification rate, resulting in concurrent variations in microstructure, including phase stability (Marya et al, 2015).…”
Section: Anisotropy and Phase Stabilitymentioning
confidence: 99%